Rapid Detection of Panton-Valentine Leukocidin in Staphylococcus aureus Cultures by Use of a Lateral Flow Assay Based on Monoclonal Antibodies - Monecke, S.; Muller, E.; Buechler, J.; Rejman, J.; Stieber, B.; Akpaka, P.; Bandt, D.; Burris, R.; Coombs, Geoffrey; Hidalgo-Arroyo, A.; Hughes, P.; Kearns, A.; et al. (American Society for Microbiology, 2013)
Panton-Valentine leukocidin (PVL) is a virulence factor of Staphylococcus aureus, which is associated with skin and soft-tissue infections and necrotizing pneumonia. To develop a rapid phenotypic assay, recombinant PVL F component was used to generate monoclonal antibodies by phage display. These antibodies were spotted on protein microarrays and screened using different lukF-PV preparations and detection antibodies. This led to the identification of the optimal antibody combination that was then used to establish a lateral flow assay. This test was used to detect PVL in S. aureus cultures. The detection limit of the assay with purified native and recombinant antigens was determined to be around 1 ng/ml. Overnight cultures from various solid and liquid media proved suitable for PVL detection. Six hundred strains and clinical isolates from patients from America, Europe, Australia, Africa, and the Middle East were tested. Isolates were genotyped in parallel by DNA microarray hybridization for confirmation of PVL status and assignment to clonal complexes. The sensitivity, specificity, and positive and negative predictive values of the assay in this trial were 99.7, 98.3, 98.4, and 99.7%, respectively. A total of 302 clinical isolates and reference strains were PVL positive and were assigned to 21 different clonal complexes. In summary, the lateral flow test allows rapid and economical detection of PVL in a routine bacteriology laboratory. As the test utilizes cultures from standard media and does not require sophisticated equipment, it can be easily integrated into a laboratory's workflow and might contribute to timely therapy of PVL-associated infections.